The mystery of appearance : conversations between ten British post-war painters - Lampert, Catherine; Hunt, Tom. (London : Haunch of Venison, 2011)
Introduction / Ben Tufnell ##The mystery of appearance / Catherine Lampert ##Conversations between ten British post-war painters : Michael Andrews ; Frank Auerbach ; Francis Bacon ; Patrick Caulfield ; William Coldstream ; Lucian Freud ; Richard Hamilton ; David Hockney ; Leon Kossoff ; Euan Uglow ##Painting inside out / Tom Hunt --
Includes bibliographical references.
boek